Nations and nationalism - Gellner, Ernest (New perspectives on the past, 2008)
First published in 1983, Nations and Nationalism remains one of the most influential explanations of the emergence of nationalism ever written. This updated edition of Ernest Gellner's now-canonical work includes a new introductory essay from John Breuilly, tracing the way the field has evolved over the past two decades, and a bibliography of...